1995
DOI: 10.1001/jama.1995.03520410054026
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer and Vascular Dementias and Driving

Abstract: Based on this study, type and degree of cognitive impairment are better predictors of driving skills than age or medical diagnosis per se. Specific testing protocols for drivers with potential cognitive impairment may detect unsafe drivers more effectively than using age or medical diagnosis alone as criteria for license restriction or revocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(55 citation statements)
references
References 28 publications
5
50
0
Order By: Relevance
“…Our study found that the AD group frequently made operational errors such as hesitant driving and diminished awareness of the traffic environment; tactical errors such as problems with changing lanes smoothly; and most strikingly, strategic judgment errors such as making a turn into a one way street. These observations coincide well with those of previous investigations of driving in early AD that also found significant declines in qualitative judgments, awareness of how driving affects others, and speed control (Duchek et al, 2003;Fitten et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…Our study found that the AD group frequently made operational errors such as hesitant driving and diminished awareness of the traffic environment; tactical errors such as problems with changing lanes smoothly; and most strikingly, strategic judgment errors such as making a turn into a one way street. These observations coincide well with those of previous investigations of driving in early AD that also found significant declines in qualitative judgments, awareness of how driving affects others, and speed control (Duchek et al, 2003;Fitten et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, few drivers in the study were affected by cognitive impairment and so a restricted range of scores on the measures of mental status would have made it unlikely that mental status was found to be related to driving performance in this study. Previous studies have found that declines in mental status are related to losses of driving ability (Clark et al, 2000;Cushman, 1996;Fitten et al, 1995;Rizzo, McGehee, Dawson, & Anderson, 2001) but that drivers affected by such declines lack the necessary insight to enact self-regulation (Adler, Rottunda, & Kuskowski, 1999;Ball et al, 1998;Eberhard, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The DBOG (Driving Behaviours Observation Grid) is a driving performance evaluation (unpublished) that was developed for a research project on the neuropsychological assessment of older drivers. Based on a literature review of studies with road tests for people with cognitive disabilities (Akinwuntan et al, 2003;De Raedt and Ponjaert-Kristoffersen, 2001;Fitten et al, 1995;Hunt et al, 1997;Janke and Eberhard, 1998;Radford, 2001), the present version was developed with the consensus of two independent experts on driving examinations. To develop a valid driving assessment for older people, the driving habits and difficulties that previous research found for this group (Ferreira et al, 2007) were also taken into account.…”
Section: Instrumentsmentioning
confidence: 99%
“…These limitations include the poor sensitivity for those scoring at the mid-range (Marcotte and Scott, 2009) and the weaker association with driving measures at the higher end of the scale (score greater than 26) (Fitten et al, 1995). In addition, the MMSE is based almost entirely on verbal cognitive function at the expense of non-dominant hemisphere skills and executive functions (Bak and Mioshi, 2007), which are the most related to various driving measures (cf., Amick et al, 2007;Daigneault et al, 2002;Lincoln et al, 2010;Reger et al, 2004;Whelihan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%